2003
DOI: 10.1108/00220410310463860
|View full text |Cite
|
Sign up to set email alerts
|

Information seeking and use by newspaper journalists

Abstract: Reports an interview study into information seeking and use by journalists at a national British newspaper. Describes work activity in the context of a series of behaviour shaping constraints and cognitive and external resources. Describes the journalist's information seeking as motivated by originality checking (of the angle), developing a personal understanding, discovering/confirming potential content and also describes information gathering and managing multiple information spaces. Shows how these are moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 11 publications
(21 reference statements)
4
65
0
2
Order By: Relevance
“…Therefore, information seeking problem was understood as synonymous with barrier. Some researchers (e.g., Attfield & Dowell, 2003) prefer the term "constraint." In the present study, the terms barrier and constraint are used synonymously, because the boundary between them tends to be elusive and they often refer to the same factors hampering information seeking in some way.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, information seeking problem was understood as synonymous with barrier. Some researchers (e.g., Attfield & Dowell, 2003) prefer the term "constraint." In the present study, the terms barrier and constraint are used synonymously, because the boundary between them tends to be elusive and they often refer to the same factors hampering information seeking in some way.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Kuhlthau and Tama [17] present findings from a study of information use by lawyers, while Attfield and Dowell [4] studied journalists' use of electronic information resources. The work reported here focuses on two contrasting domains in which the use of electronic information is relatively mature but, nevertheless, developing rapidly -namely, academia and health services.…”
Section: Introductionmentioning
confidence: 99%
“…The work has been reported in both academic papers (Attfield and Dowell, 2003) and a confidential report back to the organisation. In particular, to 'pay our way' for access to the study context, we performed and reported on a comparative usability evaluation of two digital libraries that were used within the organization.…”
Section: Reportingmentioning
confidence: 99%